Physiologic Factors Influencing the Arterial-To-End-Tidal CO2 Difference and the Alveolar Dead Space Fraction in Spontaneously Breathing Anesthetised Horses - Mosing, Martina; Böhm, Stephan H.; Rasis, Anthea; Hoosgood, Giselle; Auer, Ulrike; Tusman, Gerardo; Bettschart-Wolfensberger, Regula; Schramel, Johannes P. (Frontiers in Veterinary Science, 2018)
The arterial to end-tidal CO2 difference (P(a-ET)CO2) and alveolar dead space fraction (VDalvfrac=P(a-ET)CO2/PaCO2), are used to estimate Enghoff’s ‘pulmonary dead space’ (V/QEng), a factor which is also influenced by venous admixture and other pulmonary perfusion abnormalities and thus is not just a measure of dead space as the name suggests. The aim of this experimental study was to evaluate which factors influence these CO2 indices in anaesthetised spontaneously breathing horses. Six healthy adult horses were anaesthetised in dorsal recumbency breathing spontaneously for 3 hours. Data to calculate the CO2 indices (response variables) and dead space variables were measured every 30 minutes. Bohr’s physiological and alveolar dead space variables, cardiac output (CO), mean pulmonary pressure (MPP), venous admixture ("Q" ̇s/"Q" ̇t), airway dead space, tidal volume, oxygen consumption and slope III of the volumetric capnogram were evaluated (explanatory variables). Univariate Pearson correlation was first explored for both CO2 indices before V/QEng and the explanatory variables with rho were reported. Multiple linear regression analysis was performed on P(a-ET)CO2 and VDalvfrac assessing which explanatory variables best explained the variance in each response. The simplest, best-fit model was selected based on the maximum adjusted R2 and smallest Mallow’s p (Cp). The R2 of the selected model, representing how much of the variance in the response could be explained by the selected variables, was reported. The highest correlation was found with the alveolar part of V/QEng to alveolar tidal volume ratio for both, P(a-ET)CO2 (r = 0.899) and VDalvfrac (r = 0.938). Venous admixture and CO best explained P(a-ET)CO2 (R2 = 0.752; Cp = 4.372) and VDalvfrac (R2 = 0.711; Cp = 9.915). Adding MPP (P(a-ET)CO2) and airway dead space (VDalvfrac) to the models improved them only marginally. No ‘real’ dead space variables from Bohr’s equation contributed to the explanation of the variance of the two CO2 indices. P(a-ET)CO2 and VDalvfrac were closely associated with the alveolar part of V/QEng and as such, were also influenced by variables representing a dysfunctional pulmonary perfusion. Neither P(a-ET)CO2 nor VDalvfrac should be considered pulmonary dead space, but used as global indices of V/Q mismatching under the described conditions.